2021
DOI: 10.37899/journallalifesci.v2i1.320
|View full text |Cite
|
Sign up to set email alerts
|

Effect Jamblang Stem Barks, Mangosteen Peel, and Cinnamon to Blood Sugar Levels

Abstract: Diabetes mellitus ranks seventh as the most deadly disease with a prevalence of 1.9% and is dominated by type 2 diabetes mellitus with 95%. A solution is needed to overcome this problem, one of which is by utilizing jamblang stem barks, cinnamon, and mangosteen peel which are packaged in a popular product, namely steeping tea bags. This research aimed to determine the effect and potential biodiversity of extracts of jamblang stem barks, cinnamon and mangosteen peel as an antidiabetic drug in the form of infusi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 6 publications
(8 reference statements)
0
1
0
Order By: Relevance
“…In vivo, their activities can repair β-pancreatic cells in streptozotocin (STZ) [ 14 ]. Baladraf [ 15 ] also demonstrated that mangostin has antihyperglycemic activity in diabetic rats induced by 40% alloxan and glucose compounds in 2021. The study was conducted using Java Plum stem and mangosteen peel extracts, as well as cinnamon.…”
Section: Introductionmentioning
confidence: 99%
“…In vivo, their activities can repair β-pancreatic cells in streptozotocin (STZ) [ 14 ]. Baladraf [ 15 ] also demonstrated that mangostin has antihyperglycemic activity in diabetic rats induced by 40% alloxan and glucose compounds in 2021. The study was conducted using Java Plum stem and mangosteen peel extracts, as well as cinnamon.…”
Section: Introductionmentioning
confidence: 99%